Assessment of Environment of Pediatric Surgery Residents of Pakistan using PHEEM - Naeem Liaqat; Asif Iqbal; Sajid Hameed Dar (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2019)
Introduction: Different countries have their own residency programs in order to train new residents in the field of medicine. Some of these programs are very efficient while some have room to improve, especially in developing countries. These residency programs can play an important role in producing great consultants in the future. So it is very important to evaluate the residency program of a country so as to make sure their residents receive quality training. Materials and Methods: A cross-sectional survey was conducted in Pakistan using PHEEM questionnaire; for assessment of educational environment of pediatric surgery post graduate residents (PGR's) of Pakistan. A questionnaire was sent to all 95 pediatric surgery residents via E-mail in February 2017 and SPSS 20 was used to analyze data. Results: The response rate from pediatric surgery PGR's was 48.4% (n= 45). The mean age of participants was 29.69 ± 2.71 years. Most of the participants were male (76%) and in 5th year of residency (39.13%). The high scored items (mean >2.5) were only 3: question 9, 17 and 26. The mean PHEEM total score was found to be 63.06 ± 16.77. When categorized into global scales, most of the residents (84.4%) labeled educational environment into level 2. Mean PHEEM score was found significantly higher among female and those residing in province 'Sindh'. Conclusion: We conclude that although educational environment depends upon and varies with many factors; overall it is not reported to be satisfactory by pediatric surgery PGR's across our country. Authorities urgently need to look into the matter and take serious actions in order to improve the quality of our future consultants.